Тесла-долота трипільської культури з Наддніпров’я - Гошко, Т.Ю. (Археологія і давня історія України, 2021)
Стаття присвячена дослідженню колекції мідних тесел-долот, знайдених на поселеннях трипільської культури етапів ВІ—ВІІ і СІ, що зберігаються у Національному музеї історії України. Copper flat axes of the Szákalhát type are a fairly common type of tools in the contemporary withstages Trypillia BI—II, CI cultures of Central Europe. These tools are characterized by asymmetry of the profile — one curved side and a flat other. The collection of Trypillia metal of the National Museum of History of Ukraine contains five Szákalhát-type products from the excavations of V. Khvoyka. Due to the attribution, it was established that they originated from the settlements of Trypillia and Veremya (the last quarter of 5th millennium BC), Khalepya and Chernyakhiv (first half of 4st millennium BC). Flat axes from Trypillia, Veremia and Chernyakhiv belongs to the Szákalhát type, Városlőd variant. The axe-chisel from Halepya has no analogies. Remains of seams on the side surfaces are often shifted to a flat surface. indicating casting in a twosided form, one of the sash of which had a deeper negative than the other. Regarding the type of mold for casting flat axes from Trypillia, some questions arose. The presence of dents on its curved surface, which have been cast from a mold, may indicate the use of a model made of either wax or fired clay. Only in such a way could similar marks appear on the surface of the casting. It is concluded that the flat axel from Trypillia may have been cast according to the wax model. This technology has been known since the time of Varna Culture (5th millennium BC). But we do not know yet whether it was known to Trypillia population. The tools are cast from copper, which contains minor impurities of other metals (from tenths to thousandths parts of a percent). This corresponds to the results of spectral analysis of the similar products from Central Europe. The blade part was formed using forging: it has expanded sideways, the blade was given a more rounded shape. Sometimes the blade part was formed by the sediment of the cutting edge (Trypillia). The technology of casting flat axes blanks from the Middle Dniprо, followed by blacksmithing, does not differ from the Central European ones and is typical for the period of existence of these tools throughout their distribution. Smaller sizes and new original shapes, inherent only in the Dniprо products, indicate their local production.